Interaksi Kecemasan Matematika dan Self-Efficacy Terhadap Kemampuan Berpikir Kreatif Siswa Sekolah Menengah Pertama - Ragil Ashari; Imam Kusmaryono (Pendidikan Matematika FKIP Universitas Mataram, 2026)
The purpose of this study is to investigate the influence of math anxiety on creative thinking ability, the influence of self-efficacy on creative thinking ability, and the combined influence of math anxiety and self-efficacy on creative thinking ability in RADEC learning, as well as to investigate the interaction between math anxiety and self-efficacy in their influence on creative thinking ability among 8th-grade students studying linear equations. This study is a quantitative study using an ex-post facto approach. The sample in this study consists of 32 eighth-grade students from Class 8D at SMP Negeri 30 Semarang, selected using cluster random sampling. The instruments used were a mathematics anxiety questionnaire, a self-efficacy questionnaire, and a test of students’ creative thinking ability using linear equation material. Initial data analysis techniques included normality and linearity tests. Hypothesis testing utilized multiple linear regression and two-way ANOVA. The results of the study indicate that: (1) mathematics anxiety and self-efficacy have a simultaneous (joint) effect on students’ creative thinking ability; (2) there is an interaction between mathematics anxiety and self-efficacy in their influence on students’ creative thinking ability;